2014 11th International Conference on Fuzzy Systems and Knowledge Discovery (FSKD) 2014
DOI: 10.1109/fskd.2014.6980896
|View full text |Cite
|
Sign up to set email alerts
|

Detection of violent crowd behavior based on statistical characteristics of the optical flow

Abstract: Detection of violent crowd behavior is an important topic in crowd surveillance. Through a study on optical flow, we can find that when crowd violence occurs, the change of variance on optical flow is become large. Hence, we introduce a statistic method based on optical flow field to detect violent crowd behaviors. Our method considers the statistical characteristics of optical flow field and extracts a statistical characteristic of the optical flow (SCOF) descriptor from these characteristics to represent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…Huang, J.F. et al [19] analyzed the behavior of a violent crowd. They present a method that only measured the statistical property in video frames, and then they used a support vector machine to discriminate the video frames into two classes, i.e., normal and abnormal.…”
Section: Introductionmentioning
confidence: 99%
“…Huang, J.F. et al [19] analyzed the behavior of a violent crowd. They present a method that only measured the statistical property in video frames, and then they used a support vector machine to discriminate the video frames into two classes, i.e., normal and abnormal.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [31] generated low level descriptors by extracting features from regions characterised by higher values of optical flow. Furthermore, Huang et al [11] performed violent crowd behaviour analysis by considering only the statistical properties of the optical flow field in video data and performed classification using SVMs. Zhang et al [30] presented a violence detection framework from surveillance video streams based on a Gaussian model of optical flow; they extracted violence optical flow vectors and also used SVMs for the classification.…”
Section: Related Workmentioning
confidence: 99%
“…Violent Flows (A+SD) Type HNF [12] 56.52 + 0.33 HC HNF + BoW [19] 57.05 + 0.32 HC MoSIFT + BoW [19] 57.09 + 0.37 HC HOG [12] 57.43 + 0.37 HC HOG + BoW [19] 57.98 + 0.37 HC HOF [12] 58,53 + 0.32 HC HOF+ BoW [19] 58.71 + 0.12 HC LTP [26] 71,53 + 0.17 HC OViF [10] 76.80 + 3.90 HC ViF [10] 81.30 + 0.21 HC GMOF [30] 82.79 HC AMDN [24] 84.72 + 0.17 DL Substantial Derivative [17] 85.53 + 0.21 HC DiMOLIF [14] 85.83 HC SCOF [11] 86.37 HC ViF+OViF [7] 88.00 + 2.45 HC MoWLD+BoW [19] 88.16 + 0.19 HC MoSIFT+KDE+Sparse Coding [25] 89.05 + 3.26 HC MoWLD + Sparce Coding [29] 89.38 + 0.13 HC PSS [1] 89.50 + 0.13 HC SSS [23] 91.90 + 0.12 HC Spatiotemporal Encoder [8] 92.18 + 3.29 DL SSDLSC [27] 92.25 + 0.12 HC MoIWlD [28] 93.19 + 0.12 HC LHOG+LHOF+BoW [31] 94.31 + 1.65 HC STIFV [2] 96.40 (mean) HC Ullah et al [22] 98.00 DL…”
Section: Acronym/abbreviationmentioning
confidence: 99%
“…This approach is computationally effective to detect violence in crowded contexts and its accuracy rate is impressive (around 82.9%). Huang et al [66] studied the optical flow and found that its variance change increases in case of a crowd violence. Therefore, they suggested a statistical approach relying on optical flow fields to detect the behaviours of a violent crowd.…”
Section: Approaches Using Optical Flow Descriptorsmentioning
confidence: 99%